Design of a Peanut Skin Peeling Machine Design Based on Professional Autodesk Inventor Software - Rifki Zainur Rahman; Agus Dwi Putra; Luchyto Chandra Permadi; Ratna Fajarwati Meditama; Bella Cornelia Tjiptady (G-Tech: Jurnal Teknologi Terapan, 2024)
The aim of designing a peanut shelling machine is to make it easier for peanut farmers to make the production process more efficient. The design stage of the peanut skin peeling machine design includes analysis of data requirements and obtaining a design that suits the farmer's capacity, design design using Autodesk Inventor Professional Software and design analysis of the peanut skin peeling machine design. The results of the analysis of the peanut shelling machine frame experienced a displacement of 0.00352 – 0.01758 and a safety factor of 15 sf, with stress of -0.886 Mpa to 0.437 Mpa which was experienced at a point below the yield stress of 1.088 Mpa so that the chassis construction was declared safe. to the static load received.